OPTIMALISASI PERAN DAN FUNGSI TENAGA ADMINISTRASI SEKOLAH (TAS) DALAM PENINGKATAN KOMPETENSI SOSIAL - Yoseptry, Ricky; Wisnurat, Yuyus; Asmara Mukti, Rita; Cantika, Winda (PENDIDIKAN SAINS DAN TEKNOLOGI, 2025)
This research aims to optimize the role and function of School Administrative Staff (TAS) in improving social competence through community service programs. TAS social competencies support an inclusive and collaborative work environment, ultimately promoting educational success. The approach is a community service method through planning, organizing, implementing, and monitoring the program. At the planning stage, TAS’s needs regarding social competence were identified through surveys and focus group discussions. The organizing stage involves forming an implementation team, scheduling activities, and providing relevant resources. Implementation of the program consists of interpersonal communication training, simulation of social situations in the work environment, and intensive mentoring. The supervision stage includes continuous evaluation of the development of participants' social competence through direct observation, interviews, and filling out questionnaires. The results showed a significant increase in TAS's ability to interact more effectively with teachers, students, and parents. The discussion explained that a participatory approach, supportive leadership, and a systematic evaluation mechanism supported the success of this program. This research recommends developing similar programs on an ongoing basis to ensure TAS's role as the leading supporter in creating a harmonious and excellent service-oriented educational environment.